Development of Quran Hadith Teaching Materials in Improving Student Learning Outcomes in Madrasah Ibtidaiyah - Makrifah, Nurul; Fauzi, Nur (STIT Al-Ibrohimy Bangkalan, 2025)
Quran Hadith subjects are very important to be mastered by students considering the importance of the Quran Hadith as a source of Islamic teachings. However, the reality in Madrasah Ibtidaiyah, students do not fully understand the Quran Hadith. One of the factors is that the teaching materials used do not encourage increased student learning outcomes, therefore, it is necessary to develop Quran Hadith teaching materials to improve the learning outcomes of students. This study aims to produce a design of Quran Hadith teaching materials to improve learning outcomes, describe the implementation of Quran Hadith teaching materials that have been developed to improve learning outcomes, describe the effectiveness of developing Quran Hadith teaching materials to improve learning outcomes. This type of research is a development research with reference to the ADDIE development model which consists of five stages, including the stages of analyze, design, develop, implement, evaluate. The results of the study indicate that the design of the development of Quran Hadith teaching materials to improve learning outcomes refers to the ADDIE development model, and is based on the principles of developing teaching materials which include the accuracy of coverage and accuracy of content, completeness of components, presentation of language and appropriate illustrations. The implementation of teaching materials was carried out 4 times in a limited trial, and 6 meetings in a broad trial. The development of Quran Hadith teaching materials to improve learning outcomes was declared effective with an increase in student learning outcomes in the psychomotor aspect with an average pretest score of 73, and a post-test of 91, with an increase in N-Gain of 0.66 in the moderate category. From the cognitive aspect, the pretest results showed an average score of 68.5, the average post-test score of 85.75 with an increase in N-Gain of 0.54.